2021
DOI: 10.1111/icad.12495
|View full text |Cite
|
Sign up to set email alerts
|

Is being green what matters? Functional diversity of cavity‐nesting bees and wasps and their interaction networks with parasites in different reforestation types in Amazonia

Abstract: Understanding the processes that shape biotic interactions within biological communities helps us to develop strategies for the establishment of ecological communities and to rehabilitate the functionality of degraded environments. We evaluated the functional diversity of cavity‐nesting bees and wasps and their interaction networks established with nest parasites in different types of reforestation in Southern Amazonia. To do so, we used bee and wasp trap‐nests to sample six different types of environments: pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…This information was questioned by Penny (1982a) and herein such idea is corroborated, as this species is restricted to Central and Southwestern Brazil. Araújo et al (2021) reported several specimens reared from artificial nests of bees in the Amazonian portion of the Brazilian state of Mato Grosso which might be A. fumosellus , however detailed examination of such material was not possible at present, so the presence of this species in that state will require corroboration (R.J.P.…”
Section: Resultsmentioning
confidence: 99%
“…This information was questioned by Penny (1982a) and herein such idea is corroborated, as this species is restricted to Central and Southwestern Brazil. Araújo et al (2021) reported several specimens reared from artificial nests of bees in the Amazonian portion of the Brazilian state of Mato Grosso which might be A. fumosellus , however detailed examination of such material was not possible at present, so the presence of this species in that state will require corroboration (R.J.P.…”
Section: Resultsmentioning
confidence: 99%
“…From the mud nest of this wasp species, a single specimen of A. fumosella was reared out and presumably it had fed on the last instar larva or on the pupa of the wasp (Buys, 2008). Recently, further unspecified associations with wasps or bees were reported by Araújo et al (2021).…”
Section: Introductionmentioning
confidence: 99%